Diversity, distribution and ecology of Davallia in Sumatra (Indonesia) and the nearby small islands - MILDAWATI MILDAWATI; SOBIR SOBIR; SULISTIJORINI SULISTIJORINI; Tatik Chikmawati (Society for Indonesian Biodiversity, 2022)
Abstract. Mildawati, Sobir, Sulistijorini, Chikmawati T. 2021. Diversity, distribution and ecology of Davallia in Sumatra (Indonesia) and the nearby small islands. Biodiversitas 23: 33-42. Davallia is an epiphytic fern genus that shows high morphological variations in many characters. This genus is widely distributed in the tropics and subtropic areas. The diversity of Davallia has not been explored and recorded in many regions, including in Sumatra Island and its surrounding small islands. Therefore, this research aimed to study the diversity of Davallia species in Sumatra and the nearby small islands based on morphological variation, as well as to investigate their distribution and ecology. Samples were collected from Kerinci Seblat National Park (NP), Bukit Tiga Puluh NP, Siberut NP, Sipora Island, North Pagai Island and South Pagai, Bukit Barisan Grand Forest Park, and Bukit Barisan Selatan NP. In total, 369 specimen sheets (i.e.145 specimens from field explorations and 224 specimens from Herbarium Bogoriense collections) were examined its morphological characters. The results showed that as many as 13 species of Davallia were recorded in Sumatra and the nearby small islands. The species found are D. angustata Wall., D. corniculata T. Moore, D. denticulata (Burm. f.) Kuhn var. denticulata, D. divaricata Blume, D. heterophylla Sm., D. hymenophylloides (Bl.) Kuhn, D. parvula Wall., D. pectinata Sm., D. pentaphylla Blume, D. repens Kuhn, D. solida (G.Forst.) Sw. var. solida, D. trichomanoides Blume var. lorranii (Hance) Holttum, D. trichomanoides Blume var. trichomanoides, and D. triphylla Hook. Ten of which were new records for this location. There were 12 spesies found in Sumatra Island except D. parvula Wall. and 11 species found on the small islands around Sumatra except for D. corniculata T. Moore and D. divaricata Blume. Davallia denticulata (Burm. F.) Kuhn var. denticulata and D. solida (G.Forst.) Sw. var. solida had the largest number of specimens found. Almost all species had a random distribution pattern at altitudes of 1000-1500 m above sea level.